2007
DOI: 10.1136/hrt.2006.095208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term treatment with carvedilol on myocardial blood flow in idiopathic dilated cardiomyopathy

Abstract: Long-term treatment with carvedilol can significantly increase coronary flow reserve and reduce the occurrence of stress-induced perfusion defects, suggesting a favourable effect of the drug on coronary microvascular function in patients with IDC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 24 publications
0
26
1
Order By: Relevance
“…Absolute MBF did not change significantly after carvedilol or placebo treatment, although hyperemic blood flow showed a trend toward increase in patients receiving active treatment. CFR significantly increased after carvedilol treatment; it remained unchanged after placebo, and stress-induced regional perfusion defects decreased after active treatment (75).…”
Section: Mbf and Coronary Microvascular Dysfunctionmentioning
confidence: 91%
See 1 more Smart Citation
“…Absolute MBF did not change significantly after carvedilol or placebo treatment, although hyperemic blood flow showed a trend toward increase in patients receiving active treatment. CFR significantly increased after carvedilol treatment; it remained unchanged after placebo, and stress-induced regional perfusion defects decreased after active treatment (75).…”
Section: Mbf and Coronary Microvascular Dysfunctionmentioning
confidence: 91%
“…In a double-blind, placebo-controlled pilot trial, 16 consecutive patients with idiopathic-dilated cardiomyopathy were randomized to treatment with either carvedilol or placebo (75). Regional MBF was measured at rest and after intravenous injection of dipyridamole using PET with 13 NH 3 at baseline and after 6 mo of treatment.…”
Section: Mbf and Coronary Microvascular Dysfunctionmentioning
confidence: 99%
“…One could speculate that the inverse relation between the use of statin and RDW may be secondary to the anti-inflammatory property of statins, which further supports RDW as a marker of chronic inflammation in patients with IDC. Long-term treatment with beta blocker (carvedilol) can significantly increase coronary flow reserve and reduce the occurrence of stress-induced perfusion defects, suggesting a favourable effect of the drug on coronary microvascular function in patients with IDC (29). The known effects of β-blocking agents in heart failure includes reversing LV remodelling, increasing myocardial oxygen to supply ratio, additional mechanisms associated with vasodilatory and antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the experience of Koepfli et al (14), where a significant drug-induced increase on PETderived CFR was achieved only pooling 36 patients with coronary artery disease treated by either carvedilol or atenolol (12 week treatment), all the other clinical studies demonstrated a positive effect of carvedilol or nebivolol on CFR (Table 1) (22). The beneficial action of carvedilol on CFVR was observed in three reports, including exclusively patients with idiopathic dilated cardiomyopathy, with a therapy time duration ranging between 1 month and 6 months (16)(17)(18). In these experiences, the increase of CFVR was mainly due to the increase of maximal CBF velocity, attributable to diminution of extravascular compressive forces and of LV filling pressure (5,6), to blunted heart rate response beneficially affecting the diastolic myocardial perfusion during hyperemia (6), to alpha-adrenergic blocking action and to improved endothelial function (23,24) possibly producing a better hyperemic microvascular vasodilation..…”
Section: Third Generation Beta-blockers (With Vasodilating Action) Anmentioning
confidence: 99%
“…The influence of these two drugs on CFR has been tested in the clinical setting. The improvement of coronary microvascular function obtainable by both carvedilol (14)(15)(16)(17) and nebivolol (7,(18)(19)(20)(21) could be at least one of the substrates underlying the improvement in LV function due to both these drugs. Except for the experience of Koepfli et al (14), where a significant drug-induced increase on PETderived CFR was achieved only pooling 36 patients with coronary artery disease treated by either carvedilol or atenolol (12 week treatment), all the other clinical studies demonstrated a positive effect of carvedilol or nebivolol on CFR (Table 1) (22).…”
Section: Third Generation Beta-blockers (With Vasodilating Action) Anmentioning
confidence: 99%